Efektifitas Substitusi Albedo Semangka dalam Pembuatan Kraker Fungsional Guna Mendukung Program Pangan Berkelanjutan: The Effectiveness of Watermelon Albedo Substitution in Making Functional Crackers to Support Sustainable Food Programs - Audrica Muhammad Earlyanto; Aisha Safyra; Muhammad Agung Aprialdi; Linda Astuti (Jurnal Ilmiah Pangan Halal, 2026)
One effort to reduce the high rate of food waste, especially that which comes from food scraps, is by consuming food sufficiently and not excessively. This is in line with the Sustainable Development Goals (SDGs) point 2, Zero Hunger, which focuses on eliminating hunger, achieving food security and improved nutrition, and promoting sustainable agriculture. One underutilized food source is watermelon albedo, even though this type of material has good nutritional content and can be used as a food source, such as in making crackers. Crackers are generally made from flour and processed through fermentation and baking. The utilization of watermelon albedo as a substitute in cracker production can be done; this is consistent with several previous studies regarding the use of plant-based materials in cracker and biscuit products. The research method used was a laboratory experiment with 3 formulation standards: Ka (16.6%), Kb (33.3%), and Kc (50%). The results of proximate tests conducted at the Sartika Laboratory, Djuanda University, found contents of 10.41% moisture, 1.54% ash, 9.28% protein, 5.97% fat, and 0.92% dietary fiber. Meanwhile, the results of sensory observations indicated that the more albedo added, the more it impacted the texture, making it softer and more difficult to shape.